PENERAPAN MODEL STUDENT TEAM ACHIEVEMENT DIVISION (STAD) PADA PEMBELAJARAN MATEMATIKA SISWA KELAS VIII SMP NEGERI 2 SALING - Malik Hidayat; Sukasno S.; Efuansyah E. (LP4MK STKIP PGRI Lubuklinggau, 2020)
This study aims to determine the completeness of the mathematics learning outcomes of class VIII students of SMP Negeri 2 Saling in the 2020/2021 academic year after the Student Team Achievement Division (STAD) learning model is applied. This type of research is a pre-experimental design with a pre-test and post-test group design. The population in this study were all students of class VIII SMP Negeri 2 Saling in the academic year 2020/2021, totaling 54 students and as the research sample, namely class VIII.A one study group totaling 12 students. The data was collected by using test techniques, namely pre-test and post-test. The collected data were analyzed using t-test at the significant level α = 0.05. Based on the results of the t-test analysis with a significance level of α = 0.05, it was obtained tcount (5.9495)> ttable (2.201), so it can be concluded that the mathematics learning outcomes of class VIII students of SMP Negeri 2 Saling after being applied with the Student Team learning model Achievement Division (STAD) is significantly complete.